Konsep Diri Mahasiswa Penghafal Al-Quran Studi Fenomenologi di Yogyakarta - Nurrafiza Nurrafiza; Fitriah M. Suud (Intiqad: Jurnal Agama dan Pendidikan Islam, 2022)
Memorizing the Qur'an is the most coveted worship to be performed by every Muslim. Many have tried to memorize but not all of them have succeeded. This research aims to describe and understand self-concept in students who memorize the Qur'an at the University of Muhammadiyah Yogyakarta. In addition, this study also aims to find out the supporting factors and inhibitors in memorizing or memorizing the Qur'an in students who memorize the Qur'an at the Muhammadiyah University of Yogyakarta. The research uses a qualitative approach, with sampling techniques using snowball sampling and purposive sampling. Data is collected by observation and interview methods. Research results (1) Students who memorize the Qur'an at the University of Muhammadiyah Yogyakarta have a positive self-concept. (2) Supporting factors in memorizing the Qur'an in students who memorize the Qur'an at the University of Muhammadiyah Yogyakarta are the intention of oneself, the encouragement of parents, families, and the supportive environment. (3) Inhibiting factors in students who memorize the Qur'an at the University of Muhammadiyah Yogyakarta are mood, laziness, mobile phones, and environmental factors. This research found that self-concept is an important thing that needs to be considered by a reciter of the Qur'an.